The Terpene Synthase Gene Family of Carrot (Daucus carota L.): Identification of QTLs and Candidate Genes Associated with Terpenoid Volatile Compounds - Keilwagen, Jens; Lehnert, Heike; Berner, Thomas; Budahn, Holger; Nothnagel, Thomas; Ulrich, Detlef; Dunemann, Frank (Frontiers in Plant Science, 2017)
Terpenes are an important group of secondary metabolites in carrots influencing taste and flavor, and some of them might also play a role as bioactive substances with an impact on human physiology and health. Understanding the genetic and molecular basis of terpene synthases (TPS) involved in the biosynthesis of volatile terpenoids will provide insights for improving breeding strategies aimed at quality traits and for developing specific carrot chemotypes possibly useful for pharmaceutical applications. Hence, a combination of terpene metabolite profiling, genotyping-by-sequencing (GBS), and genome-wide association study (GWAS) was used in this work to get insights into the genetic control of terpene biosynthesis in carrots and to identify several TPS candidate genes that might be involved in the production of specific mono- and sesquiterpenes. In a panel of 85 carrot cultivars and accessions, metabolite profiling was used to identify 31 terpenoid volatile compounds in carrot leaves and roots, and a GBS approach was used to provide dense genome-wide marker coverage (>168,000 SNPs). Based on this data, a total of 30 QTLs was identified for 15 terpenoid volatiles. Most QTLs were detected for the monoterpene compounds ocimene, sabinene, β-pinene, borneol and bornyl acetate. We identified 27 genomic regions on all 9 carrot chromosomes by GWAS which are both associated with high significance (LOD ≥ 5.91) to distinct mono- and sesquiterpene substances and to TPS candidate genes, which have been identified by homology-based gene prediction utilizing RNA-seq data. In total, 65 TPS candidate gene models in carrot were identified and assigned to known plant TPS subfamilies with the exception of TPS-d and TPS-h. TPS-b was identified as largest subfamily with 32 TPS candidate genes.